Cytomegalovirus-related Complications and Management in Facial Vascularized Composite Allotransplantation: An International Multicenter Retrospective Cohort Study - Kauke-Navarro, Martin; Panayi, Adriana C; Formica, Richard; Marty, Francisco; Parikh, Neil; Foroutanjazi, Sina; Safi, Ali-Farid; Mardini, Samir; Razonable, Raymund R; Morelon, Emmanuel; Gelb, Bruce; Rodriguez, Eduardo; et al. (Transplantation, 2022)
BACKGROUND: There is a paucity of data on the impact of cytomegalovirus (CMV) serostatus and CMV infection on outcomes in facial vascularized composite allotransplantation. METHODS: This international, multicenter, retrospective cohort study presents data on CMV and basic transplant-related demographics, including pretransplant viral D/R serostatus, and duration of antiviral prophylaxis. CMV-related complications (viremia, disease), allograft-related complications (rejection episodes, loss), and mortality were analyzed. RESULTS: We included 19 patients, 4 of whom received CMV high-risk transplants (D+/R-). CMV viremia was noted in 6 patients (all 4 D+/R- patients and 2 D-/R+), mostly within the first-year posttransplant, shortly after discontinuation of antiviral prophylaxis (median 2 mo). CMV disease occurred in 2 D+/R- patients. The high-risk group experienced relatively more rejection episodes per month follow-up. None of D+/R- patients suffered allograft loss due to rejection (longest follow-up: 121 mo). CONCLUSIONS: D+/R- patients were at increased risk of CMV-related complications. Although a higher number of rejections was noted in this group, none of the D+/R- patients lost their allograft or died because of CMV or rejection. Thus, CMV D+/R- face transplantation can likely be safely performed with prophylaxis, active surveillance, and prompt treatment.
Keywords: Viremia; Antiviral Agents; Cytomegalovirus Infections; vaskularizovaná kompozitní alotransplantace; cytomegalovirové infekce; retrospektivní studie; lidé; antivirové látky; Cytomegalovirus; valganciklovir; Humans; Vascularized Composite Allotransplantation; viremie; Valganciclovir; Retrospective Studies